Assessment of quality of life in patients after COVID-19 infection: A questionnaire-based observational study - Hanumantha, Kiran Raj; Naik, Pooja; Varma, Lavanya; Varma, Manoj; Manipal, Shruthi; Sampath, Pavitra (Asian Journal of Medical Sciences, 2021)
Background: By the end of 2019, the world has witnessed a pandemic of COVID-19 caused by novel coronavirus and is referred to as SARS-CoV-2. Aims and Objectives: The purpose of our research was to show how the COVID-19 pandemic has affected patient`s quality of life after infection with the virus post recovery. Materials and Methods: It was a questionnaire based cross sectional study. Study tool included a reliability checked self-made questionnaire with 30 questions. It was disseminated through mobile and web-based social media platforms to recovered COVID-19 patients hospitalized at centre, in and around Surathkal. Sample collection was done between September 2020 to December 2020 for about 3 months duration with a total of 550 recovered patients. We found significant stress with increasing age, which was more among males and housewives. Data analyzed by the descriptive statistics association. Results: Out of 550 recovered patients, with 314 (57.1%) of them being males. The average age was 41.02 years (SD) (16.86). Gender (p=0.017), occupation (p=0.0002), and age (p=0.001) were found to be related to stress levels. Age (p=0.001), occupation (p=0.001), and gender (p=0.002) were found to be related to feelings of isolation. The majority took all precautions, such as social distancing and disinfectant use. Conclusions: Significant increase in stress with increasing age, which was more among males and housewives. Reduced quality of life in males and elderly patients of covid-19 infection predominantly because of psychological discomfort, but family and friends played a major role as coping mechanisms.